Analisis Rate of Return Investasi Pendidikan di Perguruan Tinggi - Nur Luthfi Ardhian; Sultoni Sultoni; Burhanuddin Burhanuddin (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This research aims to know the feasibility and rate of return of education investment at higher education. The design of this research uses a descriptive-comparative with a quantitative approach. The population consists of 491 respondents at the Department Education Administration, Faculty of Education, State University of Malang. The sample was determined 123 respondents use a purposive random sampling technique. Data were collected used questionnaires in Google Form and analyzed used descriptive-comparative and rate of return techniques. This research shows that the alumni's investment in this Department can be said feasible. Besides, the alumni’s rate of return has differences based on study period and gender.Abstrak: Penelitian ini ditujukan untuk mengetahui kelayakan dan tingkat pengembalian investasi pendidikan alumni Program Studi Administrasi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Malang. Rancangan penelitian ini menggunakan deskriptif-komparatif dengan pendekatan kuantitatif. Populasi terdiri dari 491 orang dan ditetapkan sampel sejumlah 123 orang dengan teknik purposive random sampling. Pengumpulan data menggunakan kuesioner dalam bentuk Google Form, dan dianalisis dengan teknik deskriptif-komparatif serta rate of return. Hasil penelitian ini menunjukkan, bahwa investasi yang dilakukan alumni di Prodi Administrasi Pendidikan FIP UM dapat dikatakan layak. Di samping itu, tingkat pengembalian investasi alumni berbeda berdasarkan masa studi dan jenis kelamin.